The co-occurrence patterns and assembly mechanisms of microeukaryotic communities in geothermal ecosystems of the Qinghai-Tibet Plateau - Yan, Bingjie; Li, Xiaodong; Qiao, Nanqian; Da, Zhen; Xu, Jiajie; Jiang, Chuanqi; Ba, Sang (Frontiers in Microbiology, 2025)
Geothermal spring ecosystems, as extreme habitats, exert significant environmental pressure on their microeukaryotic communities. However, existing studies on the stability of microeukaryotic communities in geothermal ecosystems across different habitats and temperature gradients are still limited. In this study, we used high-throughput 18S rDNA sequencing in combination with environmental factor analysis to investigate the co-occurrence patterns, assembly mechanisms, and responses to environmental changes of microeukaryotic communities in sediment and water samples from 36 geothermal springs across different temperature gradients in southern Tibet. The results show that with increasing temperature, the network stability of microeukaryotic communities in sediments significantly improved, while the stability in water communities decreased. The assembly mechanisms of microeukaryotic communities in both sediment and water were primarily driven by undominant processes within stochastic processes. Latitude and longitude were the key factors influencing changes in sediment community composition, while water temperature and electrical conductivity were the major environmental factors affecting water community composition. Additionally, the stability of the geothermal community network was closely related to its response to external disturbances: sediment communities, being in relatively stable environments, demonstrated higher resistance to disturbances, whereas water communities, influenced by environmental changes such as water flow and precipitation, exhibited greater dynamic variability. These findings not only enhance our understanding of the ecological adaptability of microeukaryotic communities in geothermal springs but also provide valuable insights into how microorganisms in extreme environments respond to external disturbances. This is especially significant for understanding how microeukaryotic communities maintain ecological stability under highly dynamic and stressful environmental conditions.